[Cp2ZrMe(12-mu-Me-1-closo-CB11HMe10)]: a transition metal complex of a highly-methylated carborane anion. - Ingleson, M; Clarke, A; Mahon, M; Rourke, J; Weller, A (2003)
[Cp2ZrMe(12-mu-Me-1-closo-CB11HMe10), isolated by methide abstraction from Cp2ZrMe2 using [CPh3][closo-HCB11Me11] displays an intermolecular Zr...H3C interaction in both the solid state and solution.